Encontro com as memórias leitoras do bibliotecário contador de histórias - Sousa, Laiana Ferreira de (2017)
This research aims to analyze the reader memories of the storyteller librarian formed throughout his family, school, academic and professional life trajectory, evaluating if they have relation with their practices as mediator of reading, especially in public and school libraries. It seeks to arouse the recollection of life stories and their interweaving with personal and professional trajectory. The theoretical references adopted include, mainly, the field of information mediation, literary reading, orality and narratives, from authors such as Martins (1994), Kleiman (1997), Quevedo (2002), Lajolo (2001), Zilberman 2003), Chartier (1996), Soares (2010), Yunes (2002), Busatto (2003), Meireles (1979), Benjamin (1994) and Almeida Junior (2010). It also seeks to understand the concepts of memory and their interrelations in Halbwachs (2006), Nora (1978), Ricoeur (2007) and Santos (2012). Furthermore, it is proposed to investigate how the actions of social mediators reading (personal and institutional) may have contributed to the literary formation of these professionals. Therefore, we analyzed the reading memories and the narratives of four storytelling librarians who work in public and school libraries in Fortaleza. The methodological choice was Oral History with an approach in Oral History of Life, using the semistructured interview to guarantee access to the oral memories of the interlocutors. From this study, it is possible to think that the presence of storytelling as a practice of mediation and promotion of reading in library process, especially in public and school libraries, comes from the relation of the librarian to reading, from its constitution as a reader until his professional training, when he is given, however, the contact with the reading practice. This research can also contribute to the constant and innovative improvement of academic training, highlighting, in the light of interviews with newly graduated librarians, the manifestations of significant learning during the realization and participation in university extension projects. In the perspective of extending the theoretical discussion about the subject, this research presents paths to be covered and studies to be deepened.